The determinants of capital structure in insurance companies Evidence from Saudi Arabia - Elmahgop, Faiza Omer (The journal of contemporary issues in business and government, 2021)
The study examines the significant determinants of the insurance companies' capital structure listed on the Saudi Stock Exchange (Tadawul) from 2010 to 2018. In this study, one dependent variable capital structure is represented by leverage and six independent variables, firm characteristics variables (profitability, growth rate, risk, size, age) and macroeconomic variable (GDP). A random effect on a panel data regression model is employed as a tool of analysis. This study attempts to fill the lack of research in Saudi insurance companies to arrive at constructive suggestions that could contribute to financial structure decisions. The results show that profitability, age and risk have a statistically significant negative effect on the capital structure. Growth rate and firm size significantly positively influence the capital structure, while gross domestic product is insignificant.